Monoubiquitination joins polyubiquitination as an esteemed proteasomal targeting signal. (11th May 2017) - Livneh, Ido; Kravtsova‐Ivantsiv, Yelena; Braten, Ori; Kwon, Yong Tae; Ciechanover, Aaron
Abstract : A polyubiquitin chain attached covalently to the target substrate has been recognized for long as the "canonical" proteasomal degradation signal. However, several proteins have been shown to be targeted for degradation following monoubiquitination, indicating that the proteasome can recognize signals other than a ubiquitin polymer. A comprehensive screen aiming at determining the extent of this mode of recognition revealed that ∼40% of mammalian and ∼20% of yeast proteins are degraded following monoubiquitination. Characterization of these proteins showed that on average, the monoubiquitinated proteins are smaller than the polyubiquitinated ones, and in humans, are less disordered. Further, proteins degraded by the two different modes belong to distinct functional groups. These findings along with detailed structural analysis of the proteasome, its ubiquitin receptors and deubiquitinating enzymes, suggest that the ubiquitin signal – its formation, recognition, editing, and removal – is far more complex and diverse than originally assumed. Also see the video abstract here:https://youtu.be/QKpN9c6Rg20 Abstract : Polyubiquitination has been regarded as the hallmark signal for proteasomal degradation. Employing a systematic screen in both human and yeast cells, numerous proteasomal substrates were shown to be degraded following monoubiquitination, suggesting that this modification is more widespread than previously thought. Importantly, these substrates demonstrate distinct structural and functional characteristics.